Diagnosis of inflammatory lesions by high-wavenumber FT-Raman spectroscopy - das Chagas e Silva de Carvalho, Luis Felipe [UNESP]; Sato, Erika Tiemi; Almeida, Janete Dias [UNESP]; Martinho, Herculano da Silva (Springer, 2011)
The Raman spectroscopy technique has been extensively used for biological sample characterization. In particular, the fingerprint spectral region (800-1,800 cm(-1)) has been shown to be very promising for optical biopsy purposes. However, limitations for the widespread use of Raman-based optical biopsy technique still persist. For example, fluorescence when one uses visible light (400-700 nm) spectral sources is often present and appears to affect the mid-IR/Raman region more than the high-wavenumber region (2,800-3,600 cm(-1)). But, both the higher wavenumber spectral region and the mid-IR/Raman region can be fluorescence-free when one uses lasers sources, which do not cause fluorescence, for example, 1,064, 830 or 785 nm sources. In addition, the Raman spectral signal of inflammatory infiltrates can influence the biopsy diagnoses and is one important source of misdiagnosis of normal versus pathological tissues. The present work seeks to evaluate whether the Raman spectra in the high-wavenumber spectral region can be used to distinguish between oral inflammatory fibrous hyperplasia (IFH) lesions and normal (NM) tissues and hence be used as a new diagnostic tool. Thirty spectra of oral IFH lesions and NM tissues from biopsies of 12 patients were analyzed using both principal components analysis (PCA) and a binary logistic regression (BLR) model. It was found that the high-wavenumber region Raman spectra can be used to discriminate between NM tissue and oral IFH tissues by analyzing the 2,800-3,050 cm(-1) (CH2 and CH3 vibrations of lipids and proteins) and 3,050-3,600 cm(-1) (CH, OH, and NH vibrations of proteins and water) spectral intensities. A simple classification model based on the relative areas of the above cited regions resulted in concordant pairs of 95.3%. Considering the standard errors in the model parameters, it was found that the sensitivity (Se) and specificity (Sp) fall in the interval 87% < Se < 100% and 73% < Sp < 93%, respectively. In addition, it has been found that the Raman scattering cross-sections in the NH, OH, and CH stretching region are more intense than in the mid-IR/Raman (fingerprint) region.
Keywords: Raman spectroscopy; Optical biopsy; Inflammatory lesions